Economic Behavior of Muslim Farmers' Trade Madzhab Shafi'i in the Perspective of Legal Sociology - Beni Ahmad Saebani; Syamsul Falah; Titing Oting Supartini (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the practice of crop trading among Muslim farmers in Cikondang Village, Cianjur, through the lens of Imam Shafi’i’s jurisprudence. Using qualitative methods, sociological observation, interviews, and content analysis, it finds that farmers’ knowledge of Shafi’i legal rulings is limited, but their trading practices generally align with Shafi’i views, including those found in Fath al-Qarib. The study concludes that crop-sale traditions among these farmers function as customary social norms consistent with Islamic law.